Serum HDL-C levels, log (TG/HDL-C) values and serum total cholesterol/HDL-C ratios significantly correlate with radiological extent of disease in patients with community-acquired pneumonia - Deniz, Omer; Tozkoparan, Ergun; Yaman, Halil; Cakir, Erdinc; Gumus, Seyfettin; Ozcan, Omer; Bozlar, Ugur; Bilgi, Cumhur; Bilgic, Hayati; Ekiz, Kudret (Clinical biochemistry, 2006)
In several studies, it was shown that there was a marked decrease in serum levels of HDL-C during infection and inflammation in general. In particular, a decrease in the level of serum HDL-C was also shown in pneumonia. Correlations between inflammatory markers such as acute phase proteins, cytokines and serum HDL-C levels were shown. However, there are no studies indicating a correlation between serum HDL-C levels and the radiological extent of the disease (RED) in community-acquired pneumonia (CAP). We hypothesized that there could be a relationship between serum HDL-C levels and RED in CAP. A case-controlled study, including 97 patients with CAP and 45 healthy subjects, was performed. Chest X-rays of CAP patients were scored for RED, and correlations were investigated between RED scores, serum lipid parameters, the erythrocyte sedimentation rate (ESR) and serum albumin levels. The mean serum HDL-C level was lower in CAP patients than in controls. A significant and negative correlation between RED scores (REDS) and serum HDL-C levels was detected ( r = −0.64, P = 0.0001). There were also significant correlations between REDS and other lipid parameters. Significant correlations between ESR and serum HDL-C levels and between ESR and other serum lipid parameters were also found. It appears that serum HDL-C levels are generally lower in CAP cases than in healthy controls. Serum HDL-C levels and serum albumin levels might decrease and serum total cholesterol/HDL-C ratios and log (TG/HDL-C) values might increase proportionally with RED in CAP patients. These results might have some significance for individuals having long-standing and/or recurrent pneumonia and other cardiovascular risk factors.